(untitled) (Modern education and development, 2025)
This article explores advancements in the control systems of mechatron modules used for pressure treatment of metals. By integrating precision sensors, adaptive algorithms, and real-time feedback mechanisms, the proposed improvements enhance the efficiency, accuracy, and reliability of metal processing. The study includes a literature review, experimental methods, results, and discussions, culminating in conclusions and suggestions for future research.